Asset and Liability Valuations and the Expectationso Financial Statement Users - Wierzbińska, Zofia (Studia Oeconomica Posnaniensia, 2014)
This paper presents the advantages and disadvantages of fair value accounting and historical cost accounting. It also describes the characteristics of financial statements users and their expectations. The purpose of the article is to indicate that due to the different expectations of users, different valuation methods should be implemented in the financial statements of different entities.